PERBAIKAN KAPABILITAS PRODUKSI PADA UKM BAWANG GORENG KEMASAN DI KOTA WISATA BATU - Mas’ud Effendi (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Brawijaya, 2016)
ABSTRACT Fried onion and garlic, which is produced in Batu as home industry, has commercial product as food ingredient. There are two home industry in Batu, SMEs MMM located in Ngaglik village and SMEs Zaky located in Pesanggarahan village. The constrain in SMEs is the lack of production capacity due to low adoption of technology and production efficiency with which production facilities still manually so that the quality and quantity of the product cannot be maximal. The need for technological innovation over the production process will be able to improve the performance and quality of health functional beverage production. The results that have been achieved in the implementation of IbM activities include facilitating the transfer of technology in the form of cutting machine and spinner which has been applied by partners, guidance on improvement of production and management system includes quality control, GMP and log book for business management, and training, socialization and mentoring improved packaging design and marketing on-line. The results showed an increase in production efficiency with shorter time, increased quality packaging and products value is higher so that SMEs can increase profits.